(untitled) (LEARNing Landscapes, 2023)
During a two-term observational study of my Secondary English Language Arts (ELA) class, I introduced “surrealism” to the existing curriculum. Jot notes, personal interviews, and a self-study comprised my data strands. The Covid-19 pandemic struck shortly before my scheduled in-person interviews. This uncertainty disrupted my doctoral study plans, but offered a valuable opportunity for critical reflection. The fears and questions prompted by the pandemic were captured in the vulnerable “safe space” of our at-home Zoom interviews. This process thus prompted my contemplation about interviews as a continued method for combatting the stagnancy of educational spaces.